Spare - Prince Harry (London Bantam, 2023)
Before losing his mother, twelve-year-old Prince Harry was known as the carefree one, the happy-go-lucky Spare to the more serious Heir. Grief changed everything. He struggled at school, struggled with anger, with loneliness?and, because he blamed the press for his mother?s death, he struggled to accept life in the spotlight.